Analisis Kinerja Ruas Jalan Akibat Adanya Aktivitas Pada Pasar : (Studi Kasus: Jalan Buncis, Kabupaten Sorong, Papua Barat Daya) - Azizah Paus Paus, Nur; Rizal S, Muh.; Tavip Maryanto, Eko; Rahayu Ning Tyas, Mellany (CV. Shofanah Media Berkah, 2025)
The Afternoon the market one of the busiet commercial centers in Aimas Regency, particularly during traffic congestion periods. The main issue observed is traffic conflicts that result in congestion. This study evaluates the capacity of jalan Buncis leading to the Afternoon Market in Aimas Regency the Afternoon Market, as well as the influence of roadside obstacles on traffic distribution. Data collection includes traffic data on traffic volume, vehicle speed, and road capacity we’re Collected through filed surveys around jalan buncis durung market activities. The analysis was performed using the Indonesia Highway Capacity Manual (MKJI) 1997.method. Surveys were conducted on theree different days og the on Monday, Thursday, and Sunday.The results show that peak traffic reached 199 vehicles/hour, with an average speed and saturation value during the morning peak of 357 vehicles/hour, while off-peak hours recorded 184 vehicles/hour, and the evening peak reached 262 vehicles/hour. Based on the analysis, the Level of Service (LOS) for Jalan Buncis in the Afternoon Market area is classified as Level A, indicating safe conditions, low traffic volume, high speed, and drivers being able to travel at their desired speed.